2021
DOI: 10.1159/000515630
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Ginger regarding Human Milk Volume and Related Clinical Outcomes: A Systematic Review of Randomized Controlled Trials

Abstract: <b><i>Background:</i></b> Ginger has been used as a galactagogue in Southeast Asian countries. However, limited evidence of its effect has been reported. This systematic review summarizes the efficacy and safety of ginger regarding human milk volume. <b><i>Methods:</i></b> A systematic review was conducted. Randomized controlled trials (RCTs) which studied the effect of ginger on human milk volume were included. The primary outcome was 24-h human milk volume. <… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Of the 24 included systematic reviews, 17% were rated as having critically low quality ( 38 , 45 , 47 , 50 ), 46% as low quality ( 2 , 30–34 , 36 , 40 , 43 , 44 , 46 , 51 ), 33% as moderate quality ( 29 , 35 , 37 , 39 , 41 , 42 , 48 ), and 4% as high quality ( 49 ) ( Table 3 ; Supplemental Table 4 ). Only a single systematic review ( 49 ) reported sources of funding of primary studies (item 10) and only 2 reviews ( 37 , 41 ) provided a list of excluded studies with explanations for exclusion (item 7).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the 24 included systematic reviews, 17% were rated as having critically low quality ( 38 , 45 , 47 , 50 ), 46% as low quality ( 2 , 30–34 , 36 , 40 , 43 , 44 , 46 , 51 ), 33% as moderate quality ( 29 , 35 , 37 , 39 , 41 , 42 , 48 ), and 4% as high quality ( 49 ) ( Table 3 ; Supplemental Table 4 ). Only a single systematic review ( 49 ) reported sources of funding of primary studies (item 10) and only 2 reviews ( 37 , 41 ) provided a list of excluded studies with explanations for exclusion (item 7).…”
Section: Resultsmentioning
confidence: 99%
“…All 3 (100%) primary studies that assessed range of motion and arm circumference and both (100%) studies that assessed perceived exertion during exercise found no statistically significant effect of ginger consumption ( 38 ). One (50%) of the 2 studies that measured human breast milk volume found a statistically significant increase with ginger consumption ( 2 , 43 ). No reviews that examined breast milk volume or physical performance conducted meta-analyses.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Evidence suggests that curcumin, ginger and fennel (all considered generally safe by the FDA, USA (https://www.accessdata.fda.gov/scripts/cdrh/cfdocs/cfcfr/ CFRSearch.cfm?fr=582.10&SearchTerm=fennel, accessed on 12 June 2023)) warrant further evaluation in high quality pre-clinical studies. Safe use of ginger and curcumin in pregnant or lactating women and in the paediatric age group is reassuring [53][54][55][56][57][58]. Comprehensive search for the evidence on the safety and efficacy, and independent assessment of the quality of a plant-derived substance/product is critical if it is to be developed for use in preterm infants.…”
Section: Discussionmentioning
confidence: 99%